AVERTEL TOLERANCE IN DOGS TESTED UNDER SUBCHRONIC CONDITIONS - T. S. Novik; V. B. Yastreb; S. I. Chukina (Российский паразитологический журнал, 2016)
Materials and methods. The results of experiments on 15 dogs showed the effect of Avertel (used at therapeutic and triple doses) on clinical status, hematological and clinical parameters. The drug was injected to dogs daily within 7 days with 24-hour interval subconsciously at a therapeutic dose of 1 ml/kg or 0,5 mg/kg of aversectine C1 and 5 mg/kg of praziquantel and at a triple dose (0,3 ml/kg – 1,5 mg/kg aversectine C1 and 15 mg/kg of praziquantel). Results and discussion. Before injection and 1,5 and 10 days after the last injection the blood samples were collected to determine the hematological and biochemical parameters. The results of observation of general health status and behavior of dogs as well as the clinical, hematological and biochemical parameters serve as evidence of good tolerance of preparation used at the recommended therapeutic and increased doses.